ZIFs-derived Hollow CoS2/N-doped Mesoporous Graphite Carbon Nanocages as an Electrochemical Sensing Platform for Hydrazine Detection in Food. Issue 4 (1st April 2023) - Yang, Jie; Zhao, Shan; Wu, Jiaying; Ling, Chengshuang; Tang, Xin; Huang, Ke; Zou, Zhirong; Yu, Huimin; Xiong, Xiaoli
Abstract : The design and construction of a promising electrode is attractive for the sensitive and selective detection of hydrazine. In this paper, hollow CoS2 /N-doped mesoporous graphite carbon nanocages (CoS2 /HNGC) were synthesized derived from ZIF-8@ZIF-67 by annealing and sulfidation. In situ nitrogen coordination and self-compounding porous carbon with hollow structure can effectively improve electrocatalytic performance and electron transfer rate of catalyst electrode. The sensor has good performance for hydrazine with a wide linear range of 1 μ M − 3 mM, high sensitivity of 2384 μ A mM −1 cm −2, and detection limit of 0.272 μ M (S/N = 3). In addition, the fine selectivity and the application of this sensor in food hydrazine detection suggest that CoS2 /HNGC can be used as an efficient electrochemical detection material for hydrazine.